AAV-mediated factor IX gene transfer to skeletal muscle in patients with severe hemophilia B - Manno, Catherine S.; Chew, Amy J.; Hutchison, Sylvia; Larson, Peter J.; Herzog, Roland W.; Arruda, Valder R.; Tai, Shing Jen; Ragni, Margaret V.; Thompson, Arthur; Ozelo, Margareth; Couto, Linda B.; Leonard, Debra G.B.; et al. (Blood, 2003)
Hemophilia B is an X-linked coagulopathy caused by absence of functional coagulation factor IX (F.IX). Previously, we established an experimental basis for gene transfer as a method of treating the disease in mice and hemophilic dogs through intramuscular injection of a recombinant adeno-associated viral (rAAV) vector expressing F.IX. In this study we investigated the safety of this approach in patients with hemophilia B. In an open-label dose-escalation study, adult men with severe hemophilia B (F.IX < 1%) due to a missense mutation were injected at multiple intramuscular sites with an rAAV vector. At doses ranging from 2 × 1011vector genomes (vg)/kg to 1.8 × 1012vg/kg, there was no evidence of local or systemic toxicity up to 40 months after injection. Muscle biopsies of injection sites performed 2 to 10 months after vector administration confirmed gene transfer as evidenced by Southern blot and transgene expression as evidenced by immunohistochemical staining. Pre-existing high-titer antibodies to AAV did not prevent gene transfer or expression. Despite strong evidence for gene transfer and expression, circulating levels of F.IX were in all cases less than 2% and most were less than 1%. Although more extensive transduction of muscle fibers will be required to develop a therapy that reliably raises circulating levels to more than 1% in all subjects, these results of the first parenteral administration of rAAV demonstrate that administration of AAV vector by the intramuscular route is safe at the doses tested and effects gene transfer and expression in humans in a manner similar to that seen in animals.